Assessment of Bank Technology Machine and Mobile Banking as Market Strategies to Raising Performance of Banks in Nigeria - Adaramola, Anthony O.; Kolapo, Funso T. (Journal of Economics and Behavioral Studies, 2019)
The market challenge in form of increasing competition for success in the banking sector calls for market strategies that are customer- based towards raising the performance of Nigerian banks. The use by banks, of Automated Teller Machines and Mobile banking are at the centre stage of this market strategy. Existing knowledge on this aspect of marketing is inadequate. This study assessed the empirical effects of Automated Teller Machine and Mobile banking as marketing tools on return on equity of banks in Nigeria. Both primary and secondary data were used in the study. The data were fitted to Panel regression models of Fixed and Random effects. Findings support increasing distribution of Teller machines and raising awareness on Mobile banking as result-oriented marketing strategy for banks.